2016
DOI: 10.1007/s00221-015-4537-9
|View full text |Cite
|
Sign up to set email alerts
|

The delayed reproduction of long time intervals defined by innocuous thermal sensation

Abstract: The presence of discrete events during an interval to be estimated generally causes a dilation of perceived duration (event-filling effect). Here, we investigated this phenomenon in the thermal modality using multi-seconds (19 s) innocuous cool stimuli that were either constant (continuous interval) or fluctuating to create three discrete sensory events (segmented interval). Moreover, we introduced a delay following stimulus offset, before the reproduction phase, to allow for a direct comparison with our recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Then these participants were asked to rate again the initial stimulus of 0.20mA before increasing the stimulus at a rate of 0.20mA per trial until they indicated a score of 6 on the NRS or until the stimulus intensity reached 4.00mA. The three stimuli selected for the verbal estimation task included the last one rated as 0 on the NRS (no pain) and the first ones rated as 3 (low pain; following Serlin, Mendoza, Nakamura, Edwards, & Cleeland, 1995) and 6 (high pain; following Khoshnejad, Martinu, Grondin, & Rainville, 2016). Verbal estimation task.…”
Section: Methodsmentioning
confidence: 99%
“…Then these participants were asked to rate again the initial stimulus of 0.20mA before increasing the stimulus at a rate of 0.20mA per trial until they indicated a score of 6 on the NRS or until the stimulus intensity reached 4.00mA. The three stimuli selected for the verbal estimation task included the last one rated as 0 on the NRS (no pain) and the first ones rated as 3 (low pain; following Serlin, Mendoza, Nakamura, Edwards, & Cleeland, 1995) and 6 (high pain; following Khoshnejad, Martinu, Grondin, & Rainville, 2016). Verbal estimation task.…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed the same procedure used in Experiment 1. Only, participants selected thermal intensities equal to 0 and 6 in the NRS (instead of 0 and 3) during the intensity rating task, that is a warm but non painful intensity and a high pain intensity (following Khoshnejad et al, 2016 ). During the temporal generalisation task, therefore, participants felt the thermode being at high pain intensity during the training phase of the two pain conditions (pain immediate and pain delay).…”
Section: Methodsmentioning
confidence: 99%